Discovery of Novel Materials with Broad Resistance to Bacterial Attachment Using Combinatorial Polymer Microarrays. (18th February 2013) - Hook, Andrew L.; Chang, Chien‐Yi; Yang, Jing; Atkinson, Steve; Langer, Robert; Anderson, Daniel G.; Davies, Martyn C.; Williams, Paul; Alexander, Morgan R.
<x xml:space="preserve">Abstract</x> A new class of bacteria‐attachment‐resistant materials is discovered using a multi‐generation polymer microarray methodology that reduces bacterial attachment by up to 99.3% compared with a leading commercially available silver hydrogel anti‐bacterial material. The coverage of three bacterial species, Pseudomonas aeruginosa, Staphylococcus aureus, and uropathogenic Escherichia coli is assessed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>